Shapes and fissility of highly charged and rapidly rotating levitated liquid drops - Liao, L.; Hill, Richard J.A. (American Physical Society, 2017)
We use diamagnetic levitation to investigate the shapes and the stability of free electrically charged and spinning liquid drops of volume ∼1 ml. In addition to binary fission and Taylor cone-jet fission modes observed at low and high charge density, respectively, we also observe an unusual mode which appears to be a hybrid of the two. Measurements of the angular momentum required to fission a charged drop show that nonrotating drops become unstable to fission at the amount of charge predicted by Lord Rayleigh. This result is in contrast to the observations of most previous experiments on fissioning charged drops, which typically exhibit fission well below Rayleigh’s limit.